First, write dy/dx = y' , so you want y' + 6y = 3.
First, you would like to get rid of that "3" there. To do so, you can do a change of variables:
Let y = z + 1/2.
Then y' = z' and 6y = 6z + 3, so z' +6z = 0.
Now, solving, you get z'/z = -6
Integrating both sides, you get ln(z) = -6x + C and so z = Ce^(-6x)
Finally, y = Ce^(-6x) + 1/2.
Using the y(0) = 0 constraint, you get 0 = C + 1/2, so C = -1/2
SO y = (-1/2)e^(-6x) + 1/2
2007-03-19 17:25:39
·
answer #1
·
answered by chiggitychaunce2 2
·
0⤊
0⤋
That is saying that if you plugged in 0 for y, the answer would become 0 =3. That is impossible. It pretty much is a domain error.
2007-03-19 17:14:03
·
answer #2
·
answered by Anonymous
·
0⤊
1⤋
dy/dx = 3 - 6y
â« [1 / (3 - 6y)].dy =â« dx
log(3 - 6y) = x + k
From boundary conditions:-
log3 = k, thus:-
log(3 - 6y) = x + log3
log(3 - 6y) - log3 = x
log(1 - 2y) = x
1 - 2y = e^(x)
2y = 1 - e^(x)
y = (1/2).[1 - e^(x) ]
2007-03-19 23:26:22
·
answer #3
·
answered by Como 7
·
0⤊
0⤋